2002
DOI: 10.1152/ajpheart.00244.2002
|View full text |Cite
|
Sign up to set email alerts
|

Probing the link between citrate and malonyl-CoA in perfused rat hearts

Abstract: Little is known about the sources of cytosolic acetyl-CoA used for the synthesis of malonyl-CoA, a key regulator of fatty acid oxidation in the heart. We tested the hypothesis that citrate provides acetyl-CoA for malonyl-CoA synthesis after its mitochondrial efflux and cleavage by cytosolic ATP-citrate lyase. We expanded on a previous study where we characterized citrate release from perfused rat hearts (Vincent G, Comte B, Poirier M, and Des Rosiers C. Citrate release by perfused rat hearts: a window on mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 45 publications
6
35
0
Order By: Relevance
“…No such correlation between tissue malonyl-CoA concentration and perfusate fatty acid concentration was observed with the other fatty acids (not shown). Our data are in agreement with results that malonyl-CoA concentration is higher in hearts perfused with octanoate than in hearts perfused with palmitate or oleate (37,38).…”
Section: Resultssupporting
confidence: 93%
“…No such correlation between tissue malonyl-CoA concentration and perfusate fatty acid concentration was observed with the other fatty acids (not shown). Our data are in agreement with results that malonyl-CoA concentration is higher in hearts perfused with octanoate than in hearts perfused with palmitate or oleate (37,38).…”
Section: Resultssupporting
confidence: 93%
“…Thus, it is unlikely that the modulation of ACC and MCD activities exerts a tight control on malonyl-CoA turnover. It was previously shown that the myocardial content of malonylCoA is elevated when acetyl-CoA levels are increased by either activation of pyruvate dehydrogenase (8,9) or by perfusing the heart with octanoate instead of palmitate or oleate (10,11). The increase in malonyl-CoA content was independent of ACC activity.…”
mentioning
confidence: 96%
“…much below the K m of ACC␤ for acetyl-CoA. It has been proposed that mitochondrial acetyl-CoA is transferred to the cytosol either via acetylcarnitine and the carnitine acetyl transferase system (14) or via citrate and ATP-citrate lyase (15,16). Arguing against the role of acetylcarnitine is the reported absence of extramitochondrial carnitine acetyl transferase in the heart (17).…”
mentioning
confidence: 99%
“…Arguing against the role of acetylcarnitine is the reported absence of extramitochondrial carnitine acetyl transferase in the heart (17). Although the activity of ATP-citrate lyase in the heart is low, it could sustain the rates of increase in malonyl-CoA concentration measured in perfused rat hearts following the addition of substrates that raise malonyl-CoA concentration (16). Also, the physiological release of citrate by the heart (18,19) implies that citrate is available to cytosolic ATP-citrate lyase after transport from the mitochondria (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation